Answer: 46 years
Step-by-step explanation:
Let the father's age be x and the son's age be y, then 3 years ago:
Father = x - 3
son = y - 3
Then , from the first statement :
x - 3 = 3 ( y - 3 )
x - 3 = 3y - 9
x = 3y - 9 + 3
x = 3y - 6 .......................................... equation 1
In five years time
father = x + 5
son = y + 5
Then , from the second statement
x + 5 = 2 ( y + 5 )
x + 5 = 2y + 10
x = 2y + 10 - 5
x = 2y + 5 ........................ equation 2
Equating equation 1 and 2 , we have
3y -6 = 2y + 5
add 6 to both sides
3y = 2y + 5 + 6
subtract 2y from both sides
3y - 2y = 11
y = 11
substitute y = 11 into equation 1 to find the value of x
x = 3y - 6
x = 3(11) - 6
x = 33 - 6
x = 27
This means that the father is presently 27 years and the son is presently 11 years.
In four years time
father = 27 + 4 = 31
son = 11 + 4 = 15
sum of their ages in four years time will be
31 + 15 = 46 years
7 3/10 + 6 1/3 + 2 7/10
First change them to improper fractions
73/10 + 19/3 + 27/10
now find the common denominator which would be 30
73/10 = 219 /30
19/3 = 190/30
27/10 = 81 /30
now add (219 + 190 + 81) = 490/30
now divide 490 ÷ 30 = 16 1/3
Your answer is 16 1/3
Hope this helps. :)
Wait what's the question tho?
is it if this point is on the line?
cause it's not
-y=mx+b
3=-6(6)-3
-3=-36-3
-3 does not equal -39
hence, point is not on the line
Answer:
-2, 4
Step-by-step explanation:
basically just move the dot the same distance on the other side